Біологічна оцінка насаджень дендропарку «Нижньостановецький» - Решетюк, О.В. (My University, 2016)
Biological valuation of plantings in the arboretum «Nyzhnostanovetskii» Arboretums are in specially category of plantings which are common used , at one time they carry out environmental protection and enlightenment functions. So, the question of studying about their modern state, improving the methodology and inventory optimization plantations, development of restoration activities and programs for conservation is extremely urgent problem. The main goal of researches - to study taxonomic and objective-spatial structure of tree plantations in Nyzhnostanovetskii park, to conduct complex biological and landscape mark, to establish the stability of park culturephytocoenosis. In future it will permit to compose the register of species and molded diversity collections in Bukovyna parks and to choose the range of decorative tree plantings for renovating and reconstructing park plantings. Systematic position of species is directed in "The keys to higher plants of Ukraine" with specification “Vascular Plants Of Ukraine: A Nomenclatural Checklist”. Comprehensive biological and landscape valuations are conducted by the recommendations of specialists from National Botanical Garden after M. Gryshko. The structure of plantings is researched by V. Vitenko, V. Shlapak, the objective-spatial by N. Tulpanov. The range of decorative tree plantings for recovering and reconstructing park plantings is proposed by the method of comparative-climate analogues modified by M. Kohno and A. Kurduk. The arboretum "Nyzhnostanovetskii" is a modern, small, combined type of Precarpathians village park which was founded in 1964 (Nyzhni Stanivtsi, Kitsman area, Chernivtsi region), like a function value – it is scientific with local protection status. Dendoflora park is presented by 33 families, 63 genus and 102 species. Most of them – are flower plants from dicotyledonous (Magnoliopsida). The biggest variety in taxonomic accessory have Rosaceae and Pinaceae families, 81 species (64,8 %) are introdutsents. An intraspecific variety of park is very low. The distribution of dendroflora park for life forms has shown an appreciable advantage of wood forms over shrubs and vines. The analysis of the taxonomic composition of coniferous and deciduous species has shown a significant predominance of deciduous over coniferous. The most numerous on the number of individuals are Carpinus betulus L., Quercus robur L. and Tilia cordata Mill. The landscape valuation of park planting was carried out and it had shown typical correlation of closed and half-opened types of landscapes (appropriately: 43 and 35%), it is typical for woodland park complexes. Sanitary-aesthetic condition of collection is appreciated by us like good (45,9 %) and quite good (23,8 %), unsatisfactory have only 13,6 % of plantings. The main volumetric-spatial structure of plantings contains ordinary (32 %) and group (30 %) plantings, arrays (19 %) are the reason of significant sagement of park squares and impossibility of some other structure elements (tapeworms, small groups) to do the function on focusing attention and aesthetics. The landscape mark has shown an advantage of group plantings for other structure elements. The biological valuation of park plantings was carried out and proved their membership to relatively resistant (45,5%), very resistant (27,3 %) and resistant (18,2 %) groups, it confirms highly recreation capacity of territory. Although, the middle class of park planting stability shows some changes which start in groups, so there is a necessity in carrying out other types of proceedings of optimization and improvement territory. Recreational indications and aesthetic state of park are satisfied. A degree of passage and viewing in most parts of the park are average. So, the objective-spatial structure of the arboretum "Nyzhnostanovetskii" contains mostly ordinary, group plantings and arrays. The biological valuation of park plantings had shown high recreation capacity of territory and stability of landscapes, middle degrees of esthetic and recreation state. There’s a necessity in taking common optimization and fractional reconstruction of the park. These events will help to adapt the arboretum in performing new functions in landscaping system of settlement, to form resistant, lasting and high decorative plantings, and to save it for using in future.
Keywords: the arboretum "Nyzhnostanovetskii", introdutsents, dendroflora, taxonomic structure, biological valuation of tree plantings, landscape and aesthetic marks, the stability of park culturefitotsenozys, reconstruction